Atypical behavior of credit: Evidence from a monetary VAR - Elena Afanasyeva (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2013)
Credit boom detection methodologies (such as threshold method) lack robustness as they are based on univariate detrending analysis and resort to ratios of credit to real activity. I propose a quantitative indicator to detect atypical behavior of credit from a multivariate system - a monetary VAR. This methodology explicitly accounts for endogenous interactions between credit, asset prices and real activity and detects atypical credit expansions and contractions in the Euro Area, Japan and the U.S. robustly and timely. The analysis also proves useful in real time.
urn:nbn:de:hebis:30:3-305838
Keywords: C11; C13; C53; E51; E58; 330; Credit; Bayesian VAR; Conditional Forecasts